Persistent Hyperparathyroidism Is a Major Risk Factor for Fractures in the Five Years After Kidney Transplantation. Issue 10 (26th August 2013) - Perrin, P.; Caillard, S.; Javier, R. M.; Braun, L.; Heibel, F.; Borni‐Duval, C.; Muller, C.; Olagne, J.; Moulin, B.
Abstract The risk of fractures after kidney transplantation is high. Hyperparathyroidism frequently persists after successful kidney transplantation and contributes to bone loss, but its impact on fracture has not been demonstrated. This longitudinal study was designed to evaluate hyperparathyroidism and its associations with mineral disorders and fractures in the 5 posttransplant years. We retrospectively analyzed 143 consecutive patients who underwent kidney transplantation between August 2004 and April 2006. The biochemical parameters were determined at transplantation and at 3, 12 and 60 months posttransplantation, and fractures were recorded. The median intact parathyroid hormone (PTH) level was 334 ng/L (interquartile 151–642) at the time of transplantation and 123 ng/L (interquartile 75–224) at 3 months. Thirty fractures occurred in 22 patients. The receiver operating characteristic (ROC) curve analysis for PTH at 3 months (area under the ROC curve = 0.711, p = 0.002) showed that a good threshold for predicting fractures was 130 ng/L (sensitivity = 81%, specificity = 57%). In a multivariable analysis, independent risk factors for fracture were PTH >130 ng/L at 3 months (adjusted hazard ratio [AHR] = 7.5, 95% CI 2.18–25.50), and pretransplant osteopenia (AHR = 2.7, 95% CI 1.07–7.26). In summary, this study demonstrates for the first time that persistent hyperparathyroidism is an independent risk factor for fractures after kidney transplantation.